2008
DOI: 10.1111/j.1460-2695.2008.01274.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue crack growth through a residual stress field introduced by plastic beam bending

Abstract: A B S T R A C TWe present predictions and measurements of fatigue crack growth rates in plastically bent aluminium 2024-T351 beams. Beam bending and fatigue were carefully controlled to minimize factors other than residual stress that could affect the fatigue crack growth rate, such as large plastic strains or residual stress relaxation. The residual stress introduced by bending was characterized by a bending method and by the slitting method, with excellent agreement between the two methods. Crack growth rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 50 publications
(107 reference statements)
1
30
0
Order By: Relevance
“…Specimens are subjected to the bending fatigue tested used by many researcher [13][14][15]. Stress intensity factor for V-notch bent specimen is expressed by the following expression [16]:…”
Section: Fatigue Crack Growth Measurementmentioning
confidence: 99%
“…Specimens are subjected to the bending fatigue tested used by many researcher [13][14][15]. Stress intensity factor for V-notch bent specimen is expressed by the following expression [16]:…”
Section: Fatigue Crack Growth Measurementmentioning
confidence: 99%
“…The presence of RS in structures can have either beneficial or detrimental effects on FCPR. A number of studies have shown that compressive RS increase the fatigue life of cracked components (Beghini & Bertini, 1990;Fleck, Smith, & Smith, 1983;Ghidini, 2007;Itoh, Suruga, & Kashiwaya, 1989;Jones, 2008)while other studies have shown that tensile RS decrease it (Liljedahl, Zanellato, Fitzpatrick, Lin, & Edwards, 2010;Ohta, Maeda, Kosuge, Machida, & Yoshinari, 1989;Ohta, McEvily, & Suzuki, 1993;Trudel, Sabourin, Lévesque, & Brochu, 2014). Thus, there is a direct correlation between the orientation of the stress component normal to the propagation plane and its influence on FCPR.…”
Section: Introductionmentioning
confidence: 99%
“…An intense debate is found in the literature between supporters of the elastic superposition method [32,57] and those who question its applicability for the prediction of FCG in RSF [5,6,7]. Moreover, other authors agree with the use of the elastic superposition method if the crack closure phenomenon is considered [58,59]. In the case of the specimens subjected to thermal or mechanical processes to relieve the RSF, the correlation between the stress intensity factor range and the FCG rate according to an empirical relationship has been successfully employed to predict FCG [4].…”
Section: Numerical Models For Fatigue Crack Growth In Residual Stressmentioning
confidence: 99%
“…Jones and Dunn [59,56] employed the Finite Element Analysis (FEA) method to compute the total stress intensity factors and analyze the FCG in RSF according to the elastic superposition method. The specimens analyzed were the Single-Edge Bend (SE(B)) [59] and cold-hole expanded [56], and the material considered was a 2024-T351 aluminum alloy.…”
Section: Numerical Models For Fatigue Crack Growth In Residual Stressmentioning
confidence: 99%
See 1 more Smart Citation